2018
DOI: 10.1007/s00726-018-2542-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the antimicrobial properties/activity of an 11-residue Lys homopeptide by alanine and proline scan

Abstract: Previous work demonstrated that lysine homopeptides adopt a polyproline II (PPII) structure. Lysine homopeptides with odd number of residues, especially with 11 residues (K11), were capable of inhibiting the growth of a broader spectrum of bacteria than those with an even number. Confocal studies also determined that K11 was able to localize exclusively in the bacterial membrane, leading to cell death. In this work, the mechanism of action of this peptide was further analyzed focused on examining the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The morphological similarity between these two structures suggests the possibility that blebs were the source of the microvesicles detected as free forms. Blebs seem to be a common bacteria response to antimicrobials, as previously described for S. enterica (Kumaresan et al, 2015), S. aureus (Carvajal-Rondanelli et al, 2018) and other Gram-negative and Gram-positive bacteria (Takenouchi and Nishino, 1991; Tagai et al, 2011; Ryu et al, 2014; Prudêncio et al, 2015; Zhang et al, 2016). On the other hand, in this study only the Gram-negative species collapsed when exposed to the product, suggesting a different response of the two kinds of bacterial envelopes to BIOCITRO ® .…”
Section: Discussionmentioning
confidence: 61%
“…The morphological similarity between these two structures suggests the possibility that blebs were the source of the microvesicles detected as free forms. Blebs seem to be a common bacteria response to antimicrobials, as previously described for S. enterica (Kumaresan et al, 2015), S. aureus (Carvajal-Rondanelli et al, 2018) and other Gram-negative and Gram-positive bacteria (Takenouchi and Nishino, 1991; Tagai et al, 2011; Ryu et al, 2014; Prudêncio et al, 2015; Zhang et al, 2016). On the other hand, in this study only the Gram-negative species collapsed when exposed to the product, suggesting a different response of the two kinds of bacterial envelopes to BIOCITRO ® .…”
Section: Discussionmentioning
confidence: 61%
“…T11F is a peptide that exhibits antimicrobial activity and that, in solution, exists in a dimeric form stabilised by the presence of a Cys residue at the N-terminus and by the regular alternation of charged and uncharged residues [6]. Alanine scanning is a standard and systematic approach to identify the contribution of amino acid residues to the peptide’s function and conformation [10,11]. Previous studies showed that alanine substitution of the positively charged residues caused a decrease in candidacidal activity, while a more dramatic reduction in activity resulted from cysteine replacement [6].…”
Section: Discussionmentioning
confidence: 99%
“…Alanine substitution has been commonly used to probe the contribution of each residue in the structure and antimicrobial activity of peptides because the substitution of a side chain residue by methyl groups provides an effective strategy for detecting the side chains responsible for secondary structure and activity [21,43]. In this study, AQ-1766 and its alanine analogs showed similar secondary structures, with a slight tendency to form helical structures, but with distortions in the CD spectra probably due to the presence of the aromatic residues, in particular tryptophan, as previously described for other peptides [34,44].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, their antibacterial activity was higher than the one of the reference peptide (AQ-1766), particularly against Gram+ bacteria. This effect can be related to the increase of the peptide’s positive net charge, associated with the lysine side chain, which is able to interact with the negatively charged bacterial membranes [43,47]. Secondly, a notorious change in the CD spectra of the lysine analogs was observed with respect to the AQ-1766 peptide and their alanine counterparts, which also suggests the lysine influence in the secondary structure.…”
Section: Discussionmentioning
confidence: 99%